Partnering in Knowledge Production: Roles for Librarians in the Digital Humanities. Issue 2 (3rd April 2021) - Bell, Emilia C.; Kennan, Mary Anne
ABSTRACT: This purpose of this paper is to review literature from the digital humanities (DH), academic librarianship, and critical librarianship, focusing on potential roles for Australian academic librarians in the DH. After defining DH and its relationship with academic librarianship, the difference between service and collaborative models is discussed. This includes how service models characterise current perceptions of DH librarians' roles. Findings of this review indicate that there are, indeed, roles for librarians in the DH that can contribute to scholarly partnerships. These roles build on the shared values of librarianship and the humanities and are related to the critical and theoretical foundations of the DH. Critical librarianship provides a framework for roles that can contribute to knowledge production, not just to service provision. This framework can also work towards increasing representation and accessibility in DH scholarship.